Hazing : destroying young lives - Nuwer, Hank (Indiana University Press, 2018)
When does becoming part of the team go too far' For decades, young men and women endured degrading and dangerous rituals in order to join sororities and fraternities while college administrators blindly accepted their consequences. In recent years, these practices have spilled over into the mainstream, polluting military organizations, sports teams, and even secondary schools. In Destroying Young Lives: Hazing in Schools and the Military, Hank Nuwer assembles an extraordinary cast of analysts to catalog the evolution of this dangerous practice, from the first hazing death at Cornell University in 1863 to present day tragedies. This hard-hitting compilation addresses the numerous, significant, and often overlooked impacts of hazing, including including sexual exploitation, mental distress, depression, and even suicide. Destroying Young Lives is a compelling look at how universities, the military, and other social groups can learn from past mistakes and protect their members going forward.